Skill Premium, Labor Supply and Changes in the Structure of Wages in Latin America - Manuel Fernandez Sierra; Julián Messina (Institute of Labor Economics (IZA), 2017)
Earnings inequality declined rapidly in Argentina, Brazil and Chile during the 2000s. A reduction in the experience premium is a fundamental driver of declines in upper-tail (90/50) inequality, while a decline in the education premium is the primary determinant of the evolution of lower-tail (50/10) inequality. Relative labor supply is important for explaining changes in the skill premiums. Relative demand trends favored high-skilled workers during the 1990s, shifting in favor of low-skilled workers during the 2000s. Changes in the minimum wage, and more importantly, commodity-led terms of trade improvements are key factors behind these relative skill demand trends.
Keywords: E24; J20; J31; 330; earnings inequality; unconditional quantile regressions; supply-demand framework; human capital